Rapid Detection of Mycotoxin Contamination (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
A compilation of 12 original research articles and a review on the development of instrumental and immunoanalytical methods for mycotoxins; on the enhancement of sample preparation and selection to improve method applicability; and on practical applications of analytical methods in laboratory fungal cultures, cereal and feed samples, surface water (as a novel matrix of mycotoxins as emerging surface water contaminants), and during mycotoxin decontamination by bacteria. Target analyte mycotoxins include aflatoxins, deoxynivalenol, diacetoxyscirpenol, fumonisins, fusarenone-X, HT-2 toxins, nivalenol, ochratoxins, sterigmatocystin, T-2 toxin, and zearalenone.